2013
DOI: 10.1111/jth.12085
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant therapy for venous thromboembolism during pregnancy: a systematic review and a meta‐analysis of the literature

Abstract: To cite this article: Romualdi E, Dentali F, Rancan E, Squizzato A, Steidl L, Middeldorp S, Ageno W. Anticoagulant therapy for venous thromboembolism during pregnancy: a systematic review and a meta-analysis of the literature. J Thromb Haemost 2013; 11: 270-81.Summary. Venous thromboembolism (VTE) is one of the most relevant causes of maternal death in industrialized countries. Low molecular weight heparin (LMWH), continued throughout the entire pregnancy and puerperium, is currently the preferred treatment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 36 publications
4
67
0
9
Order By: Relevance
“…Greer and Nelson-Piercy (2005) reported a recurrence rate of 0Á84% in women prescribed thromboprophylaxis for previous VTE, thrombophilia and/or other risk factors. Romualdi et al (2013) demonstrated a reduction in the incidence of VTE recurrence of 1Á97 (95%CI 0Á88-3Á49) in women treated with LMWH for previous VTE. Pregnant patients with either previous or current VTE were randomized to receive UFH or dalteparin; no thromboembolic complications occurred in either group and a once daily dose of dalteparin was deemed effective and safe (Pettila et al, 1999).…”
Section: Pharmacological Thromboprophylaxismentioning
confidence: 97%
“…Greer and Nelson-Piercy (2005) reported a recurrence rate of 0Á84% in women prescribed thromboprophylaxis for previous VTE, thrombophilia and/or other risk factors. Romualdi et al (2013) demonstrated a reduction in the incidence of VTE recurrence of 1Á97 (95%CI 0Á88-3Á49) in women treated with LMWH for previous VTE. Pregnant patients with either previous or current VTE were randomized to receive UFH or dalteparin; no thromboembolic complications occurred in either group and a once daily dose of dalteparin was deemed effective and safe (Pettila et al, 1999).…”
Section: Pharmacological Thromboprophylaxismentioning
confidence: 97%
“…After the first successful reports involving the use of low-molecular-weight heparins (LMWHs) for the management of antenatal VTE >20 years ago, 3,4 LMWHs have superseded unfractionated heparin as the agents of choice for this indication. Whilst extensive reviews have concluded that LMWHs are safe during pregnancy, 5,6 many uncertainties remain on how best to manage women using an LMWH for antenatal VTE, especially whether LMWH should be prescribed once or twice a day. 7 The physiological changes associated with the gravid state are known to alter the pharmacokinetics of LMWH; the glomerular filtration rate is reported to increase by up to 50% by 15 weeks' gestation.…”
mentioning
confidence: 99%
“…Although a Cochrane Review stated that there was no evidence from randomised controlled trials regarding the effi cacy of anticoagulant therapy for DVT in pregnancy [2], two systemic reviews of LMWH use in pregnant women have confi rmed their efficacy and safety, which were consistent with those in nonpregnant women [3,4]. Compared to unfractionated heparin (UFH), LMWH were associated with a substantially lower risk of adverse side eff ects, such as heparin-induced thrombocytopenia (HIT), haemorrhage, and osteoporosis [3 -7].…”
Section: Anticoagulant Therapy During Pregnancymentioning
confidence: 99%